Pengetahuan Akuntansi dan Penggunaan E-Commerce dalam Mendukung Pertumbuhan UMKM - Asri Fadila Putri; Isna Ardila (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This research study aims to examine and understand accounting knowledge and the use of e-commerce in supporting the growth of MSMEs in East Medan District. The implementation uses a qualitative perspective focused on associative relationship patterns between variables. The study population consisted of 448 MSME actors or owners who run food and beverage business units located in East Medan District. The research sample was selected purposively by referring to a number of considerations and certain criteria and obtained a total of 83 MSME actors, with the number of samples calculated using the Slovin formula. The data in this study were collected through the distribution of questionnaire instruments to respondents. Furthermore, the data were processed and analyzed using a descriptive statistical approach and multiple linear regression analysis, which was also supported by testing the validity, reliability, classical assumptions, partial tests, simultaneous tests, and the magnitude of the contribution of variables that play a role in the influenced variables. The arrangement and analysis of data in this study were carried out using SPSS version 31.00. Partially, the research shows that accounting knowledge has a significant positive contribution to the growth of MSMEs in East Medan District. Furthermore, the use of e-commerce has also been shown to have a directional and meaningful impact on the growth of MSMEs in East Medan District. Simultaneously, mastery of accounting knowledge and the use of e-commerce have shown a directional and significant influence on the growth of micro, small, and medium-sized enterprises in East Medan District.